Pengelolaan Emosi sebagai Bentuk Takziyatun Nafs dalam Film “Inside Out” - Dendeu Najla Dhiyaushshafa; Fayza Farahnaz; Muhammad Haidar Gibran; Mutiara Salsabila Nuzula; Dadan Firdaus (Indo Publishing, 2026)
This study examines the representation of emotion management in the film *Inside Out* through the perspective of *tazkiyatun nafs* (purification of the soul) as articulated by Ibn Qayyim Al-Jawziyya. The research is motivated by the importance of the ability to manage emotions as a component of human mental health and spiritual development. The film *Inside Out* was selected as the material object because it depicts the dynamics of five core emotions—Joy, Sadness, Anger, Fear, and Disgust—that influence the behavior of the protagonist, Riley. The study addresses how emotion management is represented in the film and how this representation can be understood through the concept of *tazkiyatun nafs*. It employs the theory of literary psychology and Ibn Qayyim Al-Jawziyya’s concept of *tazkiyatun nafs*, which encompasses the stages of *takhalli* (emptying/purging), *tahalli* (adorning/cultivating), and *tajalli* (manifestation/illumination). A descriptive qualitative method was used, with data collection techniques involving observation, documentation, and the recording of dialogue, scenes, and visual narratives from the film. The data were analyzed interpretatively based on the perspectives of literary psychology and Sufism. The findings indicate that *Inside Out* represents emotion management as a process of accepting and balancing the full spectrum of human emotions. Riley’s emotional journey reflects the stage of *takhalli* through awareness of inner conflict, *tahalli* through the development of a positive attitude and emotional openness, and *tajalli* through the attainment of emotional balance and inner peace. Thus, *Inside Out* not only depicts the psychological process of emotion regulation but also represents spiritual values ​​aligned with the Islamic concept of *tazkiyatun nafs*.